1H, 13C, and 15N NMR Studies of Au(III) and Pd(II) Chloride Complexes and Organometallics with 2-Acetylpyridine and 2-Benzoylpyridine. (8th November 2012) - Niedzielska, Daria; Pawlak, Tomasz; Czubachowski, Tomasz; Pazderski, Leszek
Abstract : Au(III) and Pd(II) chloride complexes with N(1), O-chelating 2-acetylpyridine (2apy) and N(1)- monodentately binding 2-benzoylpyridine (2bz′py)-[Pd(2apy)Cl2 ], [Au(2bz′py)Cl3 ], trans -[Pd(2bz′py)2 Cl2 ], as well as Au(III) chloride organometallics with monoanionic forms of 2apy or 2bz′py, deprotonated at the acetyl or benzyl side groups (2apy*, 2bz′py*)-[Au(2apy*)Cl2 ], [Au(2bz′py*)Cl2 ], were studied by 1 H, 13 C, and 15 N NMR. 1 H, 13 C, and 15 N coordination shifts (i.e., differences between the respective δ 1H, δ 13C, and δ 15N chemical shifts of the same atom in the complex and ligand molecules: Δ coord 1 H = δ complex 1 H - δ ligand 1 H, Δ coord 13 C = δ complex 13 C - δ ligand 13 C, Δ coord 15 N = δ complex 15 N - δ ligand 15 N ) were discussed in relation to the molecular structures and coordination modes, as well as to the factors potentially influencing nuclear shielding. Analogous NMR measurements were performed for the new (2bz′pyH)[AuCl4 ] salt.